2019
DOI: 10.1177/0950017019866643
|View full text |Cite
|
Sign up to set email alerts
|

It’s Not All about the Economy Stupid! Immigration and Subjective Well-Being in England

Abstract: While much is known regarding the effects of immigration for objective outcomes, relatively little is known regarding the effects for perceived well-being. By exploiting spatial and temporal variation in the net-inflows of foreign-born individuals across local areas in England, we examine the relationship between immigration and natives’ subjective well-being as captured by the General Health Questionnaire (GHQ). We find small negative effects overall but that an analysis of the main effects masks significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(48 reference statements)
2
4
0
Order By: Relevance
“…Ivlevs and Veliziotis (2018) find no main effect of inflows of Eastern European immigrants in local areas on natives' life satisfaction following the 2004 enlargement that resulted in an unprecedented wave of Eastern European workers relocating to the UK. Consistent with Howley et al (2020), they observed that local immigration was associated with a decrease in life satisfaction among older, unemployed, and lower-income people, and with an increase in life satisfaction among younger, employed, higher-income, and better educated people. The heterogeneous impact is congruent with voting patterns in the Brexit vote.…”
Section: The Impact Of Migration On the Happiness Of Hosting Populationssupporting
confidence: 59%
See 2 more Smart Citations
“…Ivlevs and Veliziotis (2018) find no main effect of inflows of Eastern European immigrants in local areas on natives' life satisfaction following the 2004 enlargement that resulted in an unprecedented wave of Eastern European workers relocating to the UK. Consistent with Howley et al (2020), they observed that local immigration was associated with a decrease in life satisfaction among older, unemployed, and lower-income people, and with an increase in life satisfaction among younger, employed, higher-income, and better educated people. The heterogeneous impact is congruent with voting patterns in the Brexit vote.…”
Section: The Impact Of Migration On the Happiness Of Hosting Populationssupporting
confidence: 59%
“…To illustrate, Betz and Simpson (2013) find that a 10% increase in the immigrant inflow (at the sample mean) in Europe increases the happiness of natives by 0.07 points on an 11-point scale in the following year while no positive effects were observed after the second year. Howley et al (2020) find that an increase of 100,000 foreign-born individuals in the UK leads to a happiness decline of 0.025 points on a 37-point scale. Akay et al (2014) find that a 1 percentage point increase in the immigrant share in a local area results in a 0.03 increase on an 11-point life satisfaction scale.…”
Section: The Impact Of Migration On the Happiness Of Hosting Populationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, looking specifically into German data, Akay et al (2014) identified the same relation, specifying that the positive effect of immigration on natives' life satisfaction depends on the assimilation of immigrants in the region. Analysing British data, we also see that, in general, groups anti-immigration are made of relatively older individuals, those with below-average household incomes, the unemployed and those without any formal education as well (Howley et al, 2019). Table 1 reveals that immigration is better viewed in bigger centres.…”
Section: Immigration and Patriotismmentioning
confidence: 82%
“…Such a difference is in agreement with Zahl-Thanem and Haugen (2019), who found Norwegians in the countryside express more negative attitudes towards immigrants and immigration. If, as we have seen in subsection 4.2, rural people go through more financial hardship in life, then, considering Howley et al (2019), it would make sense to expect them to be less favourable to immigration. Isolation can play a role too: maybe we are afraid of what we do not know.…”
Section: Immigration and Patriotismmentioning
confidence: 98%